2013
DOI: 10.1186/1471-2334-13-205
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of methicillin-resistant staphylococcus aureus in the long term care facilities in Hong Kong

Abstract: BackgroundThe relative contribution of long term care facilities (LTCFs) and hospitals in the transmission of methicillin-resistant Staphylococcus aureus (MRSA) is unknown.MethodsConcurrent MRSA screening and spa type analysis was performed in LTCFs and their network hospitals to estimate the rate of MRSA acquisition among residents during their stay in LTCFs and hospitals, by colonization pressure and MRSA transmission calculations.ResultsIn 40 LTCFs, 436 (21.6%) of 2020 residents were identified as ‘MRSA-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 42 publications
2
47
3
Order By: Relevance
“…The MRSA prevalence we observed was lower than in MRSA surveys in recent years in the US [41][42][43][44][45], China [46], the UK [16], France [20], Ireland [15], and Italy [24], but higher than in the Netherlands and Sweden [14,22] (Table 3). …”
Section: Discussioncontrasting
confidence: 66%
“…The MRSA prevalence we observed was lower than in MRSA surveys in recent years in the US [41][42][43][44][45], China [46], the UK [16], France [20], Ireland [15], and Italy [24], but higher than in the Netherlands and Sweden [14,22] (Table 3). …”
Section: Discussioncontrasting
confidence: 66%
“…used molecular typing to show a high similarity between MRSA strains isolated from surveillance cultures and clinical cultures collected from patients on dialysis treatment [30]. And a study conducted at long-term care facilities in Hong Kong reported a significant dissemination of MRSA, reinforcing the need to adopt measures to reduce the transmission of this microorganism [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intravenous vancomycin is now administered for prophylaxis instead of cefazolin. 26 There are many potential risk factors for PJI documented in the literature. Nonetheless, only a limited number were included in this study, most of which are not be modifiable.…”
Section: Risk Factor Onset Of Infectionmentioning
confidence: 99%